Patient preferences and experiences of participation in surgical cancer care. Issue 5 (24th May 2022) - Drott, Jenny; Fomichov, Victoria; Nordén, Maria; Larsson, Anna Lindhoff; Sandström, Per; Björnsson, Bergthor; Eldh, Ann Catrine
Abstract: Background: Quality cancer care necessitates opportunities for patient participation, supposedly recognizing the individual's preferences and experiences for being involved in their health and healthcare issues. Previous research shows that surgical cancer patients wish to be more involved, requiring professionals to be sensitive of patients' needs. Aims: To explore preference‐based patient participation in surgical cancer care. Methods: A cross‐sectional study was conducted. The Patient Preferences for Patient Participation tool (4Ps) was used, which includes 12 attributes of preferences for and experiences of patient participation. Data were analyzed with descriptive and comparative statistical methods. Results: The results are based on a total of 101 questionnaires. Having reciprocal communication and being listened to by healthcare staff were commonly deemed crucial for patient participation. While 60% of the patients suggested that taking part in planning was crucial for their participation, they had experienced this only to some extent. Learning to manage symptoms and phrasing personal goals were items most often representing insufficient conditions for preference‐based patient participation. Linking Evidence to Action: To support person‐centered surgical care, further efforts to suffice preference‐based participation are needed, including opportunities for patients to share their experiences and engage in the planning of healthcare activities.